2015
DOI: 10.1136/tobaccocontrol-2015-052319
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden from smoking-related diseases in Thailand

Abstract: The total economic loss from smoking-related diseases highlights the significant loss to the society, health sector and the country's economy. Such information is crucial for informing national public health policy, particularly when a conflict arises between the economy and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
1
39
0
2
Order By: Relevance
“…3 When chronic airway diseases got attention in movies, scenes mostly featured people suffering from asthma, 7 a disease that is already widely known by the general audience but only partly related to smoking. Contrasting to the major worldwide health and economic impact of smoking-related diseases, 8,9 a PubMed search (performed on 28 March 2016 by JFMvB) on the keywords COPD+movies yielded a mere nine hits, of which zero were considered relevant after reading the title and the abstract. Similarly, searches on lung cancer+movies or cardiovascular disease+movies returned few relevant hits.…”
mentioning
confidence: 99%
“…3 When chronic airway diseases got attention in movies, scenes mostly featured people suffering from asthma, 7 a disease that is already widely known by the general audience but only partly related to smoking. Contrasting to the major worldwide health and economic impact of smoking-related diseases, 8,9 a PubMed search (performed on 28 March 2016 by JFMvB) on the keywords COPD+movies yielded a mere nine hits, of which zero were considered relevant after reading the title and the abstract. Similarly, searches on lung cancer+movies or cardiovascular disease+movies returned few relevant hits.…”
mentioning
confidence: 99%
“…There is indisputable evidence that tobacco use is a substantial public health concern with considerable economic ramifications [1][2][3][4] . The World Health Organization reports that global smoking-related diseases cost US$1911 billion per year and that by 2030 more than 8 million people will die annually from tobacco use 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies may explain the observed effective interventions by countries to reduce the prevalence of smokers and exhibited positive results in decreasing the mortality and morbidity associated with smoking 10,11 . However, the new data show that most countries are still faced with an increase in the number of young smokers, new cancer cases and high expenditure of cancers treatment 12,13 . Important tools to evaluate the burden of smoking related cancer is quantifying the economic burden of cancers associated to tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Most of updated studies about estimating the economic burden of cancers related to tobacco have been conducted in developed countries 10,15 and the research on this field in developing world less conducted 13,16 . Estimating the burden of selected cancers due to tobacco smoking is very pivotal in order to plan and create of effective efforts aimed at decreasing the prevalence of active smoking.…”
Section: Introductionmentioning
confidence: 99%